A Phytochemical–Halogenated Quinoline Combination Therapy Strategy for the Treatment of Pathogenic Bacteria. Issue 7 (15th May 2015) - Abouelhassan, Yasmeen; Garrison, Aaron T.; Bai, Fang; Norwood, Verrill M.; Nguyen, Minh Thu; Jin, Shouguang; Huigens, Robert W.
Abstract With the continued rise of drug‐resistant bacterial infections coupled with the current discouraging state of the antibiotic pipeline, the need for new antibacterial agents that operate through unique mechanisms compared with conventional antibiotics and work in synergy with other agents is at an all‐time high. We have discovered that gallic acid, a plant‐derived phytochemical, dramatically potentiates the antibacterial activities of several halogenated quinolines (up to 11 800‐fold potentiation against Staphylococcus aureus) against pathogenic bacteria, including drug‐resistant clinical isolates. S. aureus demonstrated the highest sensitivity towards gallic acid–halogenated quinoline combinations, including one halogenated quinoline that demonstrated potentiation of biofilm eradication activity against a methicillin‐resistant S. aureus (MRSA) clinical isolate. During our studies, we also demonstrated that these halogenated quionlines operate through an interesting metal(II) cation‐dependent mechanism and display promising mammalian cytotoxicity.